2018
DOI: 10.1186/s40645-018-0198-1
|View full text |Cite
|
Sign up to set email alerts
|

Silicate solution, cation properties, and mass transfer by aqueous fluid in the Earth’s interior

Abstract: Aqueous fluids in the Earth's interior are multicomponent systems with silicate solubility and solution mechanisms strongly dependent on other dissolved components. Here, solution mechanisms that describe the interaction between dissolved silicate and other solutes were determined experimentally to 825°C and above 1 GPa with in situ vibrational spectroscopy of aqueous fluid while these were at high temperature and pressure. The silicate content in Na-bearing, silicate-saturated aqueous fluid exceeds that in pu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
4
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 35 publications
1
4
0
Order By: Relevance
“…The observation of this band in the NaOH solution (Fig. 4b) was consistent with that reported by Mysen (2018). The band was detected above ~ 300-400 °C in the Na 2 CO 3 solution, ~ 500 °C in the NaOH solution, and ~ 600 °C in pure H 2 O.…”
Section: The ~ 600 CM −1 Band Regionsupporting
confidence: 90%
See 1 more Smart Citation
“…The observation of this band in the NaOH solution (Fig. 4b) was consistent with that reported by Mysen (2018). The band was detected above ~ 300-400 °C in the Na 2 CO 3 solution, ~ 500 °C in the NaOH solution, and ~ 600 °C in pure H 2 O.…”
Section: The ~ 600 CM −1 Band Regionsupporting
confidence: 90%
“…The Raman spectra revealed the presence of neutral monomers Si(OH) 4 and deprotonated monomers Si(OH) 3 O − in the solutions, but lacked evidence of silica oligomers in the spectral region of interest (> ~ 700 cm −1 for the observation of carbon species). On the other hand, a Raman spectroscopy study with SiO 2 -NaOH-H 2 O systems by Mysen (2018) showed the Q 1 -species band under high P-T conditions, but the presence of anionic silica species in the solution is still uncertain. Thus, the information available on the Raman observations is insufficient to understand silica solubility and speciation in Na 2 CO 3 and NaOH solutions under high P-T conditions.…”
Section: Introductionmentioning
confidence: 99%
“…In comparison, S dissolves in metal alloys as Fe–S with vibration modes at 310 and 360 cm −1 , and in silicate melts as Fe–, Mg–, and Ca–S with vibration modes between 285 and 350 cm −1 (66). Although the vibration modes of complexes involving N or S have been determined for quenched silicate and metal, their equivalents in silicate melts and liquid metals at HP–HT are expected to vary only by a few cm −1 , as shown by Mysen (71) for the N 2 vibration mode in silicate melts and aqueous fluids. The observed vibration modes are directly related to the reduced masses µ N and µ S of the bonds formed by N and S, respectively, in the metal and silicate phases.…”
Section: The Effects Of Fo2 and N Speciation On ∆15nmetal-silicatementioning
confidence: 99%
“…The high solubility obtained by using the SIT database is too high compared to values reported at 300 °C taking crystalline silica only as the equilibrium phase [63]. Mysen [64] observed a reduced solubility of silica in deeper crustal fluid in presence of Ca-rich basic rocks corresponding to deeper crust. In that context, high solubility obtained in the present case at 300 °C in the presence of anorthite needs to be confirmed.…”
Section: Geochemical Modellingmentioning
confidence: 64%